Tindakan Ibu Rumah Tangga dalam Penerapan Indikator PHBS Tidak Merokok di dalam Rumah (Studi Kualitatif di Wilayah Kerja Puskesmas Pasirian) (The Housewife Behavior in the Implementation Indicators PHBS No Smoking in The House (a Qualitative Study in Pus - Nurike Hanani Mahardika; Novia Luthviatin; Iken Nafikadini (UPT Percetakan dan Penerbitan Universitas Jember, 2017)
AbstractPHBS (Perilaku Hidup Bersih dan Sehat) tatanan rumah tangga/ Behaviour of Healthy Household is a national program that aims to enable the society to maintain and improve the health status of the society. The achievement of indicator no smoking in the house has the lowest achievement in the Center Health District Pasirian. The purpose of this study is to analyze the actions of housewives in the application of indicator PHBS no smoking in the house. This research is a qualitative descriptive research. Determination of informants in this study using purposive techniques. Techniques of collecting through in-depth interviews and triangulation of sources. The result of the research stated that the informant get knowledge about smoking only from cigarette pack. The rejection of informants in husbands who smoke is to give warning and do not give support to the husband of the informant who smoked. The informant's husband sometimes tells his son to buy a cigarette. In the implementation, informants have constraints in the application of no smoking in the house, that caused informants not to be able to implement no smoking in the house.Keywords: PHBS, household, housewife, Eradication Mosquito, No Smoking in The House